(untitled) (Development Engineering Conferences Center Articles Database, 2025)
The development of smart packaging technologies has introduced innovative approaches to real-time food spoilage detection. Among these, gold nanoclusters (AuNCs) have emerged as highly sensitive and biocompatible materials due to their unique photoluminescent properties and molecular-like behavior. This review explores the role of ligand engineering in enhancing the selectivity of AuNCs toward key spoilage gases such as ammonia (NH₃), hydrogen sulfide (H₂S), and trimethylamine (TMA). By employing diverse ligands including proteins, peptides, DNA, and polyphenols AuNCs can be tailored for specific gas recognition, enabling fluorescence-based detection mechanisms. The integration of AuNCs into biodegradable packaging films offers a non-invasive, eco-friendly solution for freshness monitoring. Comparative analysis with conventional nanomaterials highlights the superior photostability, selectivity, and sustainability of AuNCs. Despite current challenges in synthesis scalability and regulatory frameworks, ligand-engineered AuNCs represent a promising frontier in nanotechnology-driven food safety and biosensing applications. Future research should focus on hybrid nanostructures and advanced sensor platforms to accelerate their industrial deployment.